Milk Urea Nitrogen relationship with reproductive and productive parameters in Holstein, Jersey and their crosses (UNED Research Journal, 2016)
Milk Urea Nitrogen (MUN) concentration of 554 Holstein cows, 474 Jersey cows and 454 HxJ crossed cows were determined and related to the days of lactation, daily milk production, days open and calving interval. A milk sample of 100 ml was taken and analyzed by an enzyme urease kit. The Jersey breed exceeded Holstein in 2.49 and HxJ in 3.82 mg/dl. No differences in the MUN content were determined as the days of milk production. Animals with daily production below 40 liters of milk had a MUN 1.84 mg/dl lower than animals with production over 40 liters (18.17 mg/dl). MUN value did not vary according to open days, however, animals with over 360 days in interval calving showed a MUN average of 16.91 mg/dl, which exceeds 1 mg/dl animals presenting values below 360 days interval calving. Holstein and Jersey cows are more likely to have a higher MUN than HxJ crosses. It is necessary to increase the analysis of data from production systems with different management and feeding methods to generate a diagnostic tool that can be applied in dairy production systems in Costa Rica.
Keywords: Milk Urea Nitrogen; breed; calving interval; open days; lactation period; milk production